Rancang Bangun Sistem Keamanan Pintu Rumah Menggunakan Sidik Jari Sensor Dan Arduino (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
Home is an important place for most people, where they need to keep it safe and comfortable from outside interference. Therefore, there is a need for a security system that is able to protect against these disturbances. In this study, fingerprints were used to secure the door of the house, where in the process only the registered fingerprint was allowed to open the door. In table 1 it turns out that wet, wrinkled and peeling fingerprints can still be used and read by the sensor so that concerns that fingerprints cannot be used are refuted. In table 1 it is also proven that the process of opening the door can be done with an Arduino and a fingerprint sensor